2021
DOI: 10.3390/md19120671
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Physical Culture Conditions Significantly Influence the Cell Mass and Docosahexaenoic Acid Content of Aurantiochytrium limacinum Strain PKU#SW8

Abstract: Thraustochytrids are well-known unicellular heterotrophic marine protists because of their promising ability to accumulate docosahexaenoic acid (DHA). However, the implications of their unique genomic and metabolic features on DHA production remain poorly understood. Here, the effects of chemical and physical culture conditions on the cell mass and DHA production were investigated for a unique thraustochytrid strain, PKU#SW8, isolated from the seawater of Pearl River Estuary. All the tested fermentation parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…To understand the effect of nitrogen concentration on the biomass and DHA production of PKU#SW8, different concentrations (0–1.2 g/L) of monosodium glutamate (MSG) in the culture medium were tested. MSG has been reported to be one of the optimal nitrogen sources for high yields of DHA (g per g biomass) produced by thraustochytrids [ 7 , 17 , 33 ]. A defined nitrogen source such as MSG can generally be easily utilized by microorganisms for rapid cell growth and the glutamate can be converted into other nitrogen-containing compounds [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the effect of nitrogen concentration on the biomass and DHA production of PKU#SW8, different concentrations (0–1.2 g/L) of monosodium glutamate (MSG) in the culture medium were tested. MSG has been reported to be one of the optimal nitrogen sources for high yields of DHA (g per g biomass) produced by thraustochytrids [ 7 , 17 , 33 ]. A defined nitrogen source such as MSG can generally be easily utilized by microorganisms for rapid cell growth and the glutamate can be converted into other nitrogen-containing compounds [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Owing to their high lipid content, thraustochytrids have potential biotechnological applications, particularly in the nutraceutical and biofuel industries [ 3 ]. Certain thraustochytrids, namely the strains that belong to Aurantiochytrium (formerly Schizochytrium ) genus, have shown the unique ability to accumulate large amounts of polyunsaturated fatty acids (PUFAs), especially docosahexaenoic acid (DHA) [ 4 , 5 , 6 , 7 , 8 ]. In addition to PUFAs, some studies have also suggested the high potential of thraustochytrids to accumulate saturated fatty acids (SFAs) [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular lipid content and lipid yield were 62.2% and 0.205 g/g glucose, respectively, using a medium with a carbon to nitrogen (C/N) molar ratio of 6.1 and a C/P molar ratio of 9,552 ( 46 ), which means that the accumulation of lipid can also be regulated by limiting phosphorus in the medium. As a consequence, the regulation of phosphorus and sulfur limitation is of great significance for the production of lipids from nitrogen-rich crude materials ( 41 , 45 , 47 , 48 ).…”
Section: Regulation Of Fungal Fatty Acid Fermentationmentioning
confidence: 99%
“…PKU#Sw8, the increase in DHA production coincided with the up-regulation of gene expression under nitrogen-deficient culture conditions ( 44 ). Chen et al ( 45 ) optimized the culture of Thraustochytrid sp. PKU#SW8 under optimal culture conditions (glycerol, 20 g/L; peptone, 2.5 g/L; 80% seawater; pH 4.0; 28°C), the cell mass, DHA concentration and yield of PKU#SW8 were increased to 7.5 ± 0.05 g/L, 2.14 ± 0.03 g/L and 282.9 ± 3.0 mg/g, respectively, on a 5-L scale fermentation.…”
Section: Regulation Of Fungal Fatty Acid Fermentationmentioning
confidence: 99%